A comparative analysis of fuzzy-based AHP derived MCDM methods to select the apt heterogeneous wireless network. (2016) - Sasirekha, V.; Ilangkumaran, M.; Sakthivel, G.
The selection of the most appropriate network in heterogeneous wireless environment is one of the critical issues to provide the best quality of service (QOS) to the users. The selection of an apt network among various alternatives is a kind of multi criteria decision making (MCDM) problem. The aim of this paper is to describe the applications of three MCDM methods for solving the network selection problem. Fuzzy analytic hierarchy process (FAHP)- VlseKriterijumska Optimizacija I Kompromisno Resenje in Serbian (VIKOR), FAHP-technique for order preference by similarity to ideal solution (TOPSIS) and FAHP-preference ranking organisation method for enrichment evaluation (PROMETHEE) are proposed to choose the best network among the various network alternatives. The ranking performance of various MCDM methods is also compared with each other. This study comprises five alternatives such as wireless local area network (WLAN), general packet radio service (GPRS), universal mobile telecommunication (UMTS), code-division multiple-access (CDMA), worldwide interoperability for microwave access (WIMAX) and ten evaluation criteria namely bandwidth, latency, jitter, throughput, bit error rate, packet loss, re-transmission, cost, security and preference to select the appropriate network.